PENINGKATAN KEMAMPUAN REPRESENTASI MATEMATIS MELALUI MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE - Yunni Arnidha (Universitas Muhammadiyah Pringsewu, 2016)
This study aims to analyze the improvement of students' mathematical representation achievement taught by cooperative learning think pair share and students' mathematical representation achievement taught by conventional method. This study is quasi experimental with Pretest -Posttest Control Group Design. This study conducted at SMPN 3 Pringsewu. The population was all of the eight grade students at SMPN 3 Pringsewu, with the samples of this study consists of the VIII-2 class as the experiment class and VIII-5 class as the control class. To obtain the data, it used mathematical representation achievement test instrument. The data analysis was conducted to know the average difference between two samples using t-test. The result showed the improvement of mathematical representation achievement taught by cooperative learning think pair share is better than the students taught by conventional learning method. Keywords: think pair share model, conventional learning method, Mathematical representation